176k views
2 votes
Lets evaluate (3^6)^1/2

step by step.

User Deitra
by
5.5k points

2 Answers

0 votes


\displaystyle\bf \boldsymbol{\boxed{(a^n)^m=a^(n\cdot m)}} \\\\(3^6)^{(1)/(2)} =3^{(6)/(2) }=3^3=\boldsymbol{{\boxed {27}}}

User Sarmun
by
4.0k points
2 votes

Answer:

27

Explanation:


\bigg(3^6\bigg)^{(1)/(2)}

use


(a^n)^m=a^(n\cdot m)


\bigg(3^6\bigg)^{(1)/(2)}=3^{6\cdot(1)/(2)

simplify


6\!\!\!\!\diagup^3\cdot(1)/(2\!\!\!\!\diagup_1)=3\cdot(1)/(1)=3\cdot1=3

other


6\cdot(1)/(2)=(6\cdot1)/(2)=(6)/(2)=3

therefore


\bigg(3^6\bigg)^{(1)/(2)}=3^{6\cdot(1)/(2)}=3^3=\underbrace{3\cdot3\cdot3}_(3)=27

User BlackCow
by
4.2k points